The emergence of pathogenic TNF/iNOS producing dendritic cells (Tip-DCs) in a malaria model of acute respiratory distress syndrome (ARDS) is dependent on CCR4 - Galvão-Filho, Bruno (Mucosal Immunol, 2019)
Malaria-associated acute respiratory distress syndrome (MA-ARDS) and acute lung injury (ALI) are complications that cause lung damage and often leads to death. The MA-ARDS/ALI is associated with a Type 1 inflammatory response mediated by T lymphocytes and IFN-γ. Here, we used the Plasmodium berghei NK65 (PbN)-induced MA-ALI/ARDS model that resembles human disease and confirmed that lung CD4(+) and CD8(+) T cells predominantly expressed Tbet and IFN-γ. Surprisingly, we found that development of MA-ALI/ARDS was dependent on functional CCR4, known to mediate the recruitment of Th2 lymphocytes and regulatory T cells. However, in this Type 1 inflammation-ARDS model, CCR4 was not involved in the recruitment of T lymphocytes, but was required for the emergence of TNF-α/iNOS producing dendritic cells (Tip-DCs) in the lungs. In contrast, recruitment of Tip-DCs and development of MA-ALI/ARDS were not altered in CCR2(−/)(−) mice. Importantly, we showed that NOS2(−/)(−) mice are resistant to PbN-induced lung damage, indicating that reactive nitrogen species produced by Tip-DCs play an essential role in inducing MA-ARDS/ALI. Lastly, our experiments suggest that production of IFN-γ primarily by CD8(+) T cells is required for inducing Tip-DCs differentiation in the lungs and the development of MA-ALI/ARDS model.